Altruisme Relawan Search and Rescue (SAR) Kota Parepare Dalam Pelaksanaan Operasi Pencarian Dan Pertolongan - Annisa, Annisa; Suhaeb , Firdaus W; Mappe, Ulfa Utami (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
This study explores the factors which affects the altruistic behavior of Parepare City SAR volunteers. This study uses a qualitative approach of the descriptive type. In this study, there were 11 informants who were Parepare City SAR volunteers from BPBD agencies, the Fire Service, the SAR Brimob Battalion B Pioneer Satbrimob of the South Sulawesi Police and the Lasinrang SAR community, the Hidayatullah SAR and the Parepare City Fellow Care Movement who were selected using the purposive sampling technique. In this study, the data collection techniques used are observation, interviews and documentation. Checking the validity of the data using the source triangulation technique. Then the data analysis techniques used are data reduction, data display and conclusion drawn. This study found that the factors that affect the altruistic behavior of Parepare City SAR volunteers are caused by three factors, namely internal factors consisting of mood, rewarding, empathy and then external factors consisting of gender, relationship closeness, time pressure, number of observers, environment, attribution and personal factors consisting of gender, personality traits, and religiosity.